Clinical Study of Mastoid Abscess - Our Experience - Begh, Raies Ahmad; saraf, Aditiya (International Journal of Innovative Research in Medical Science, 2019)
Aims and Objectives: To study various aetiologies of mastoid abscess. Material and methods: The present study was conducted in Department of ENT, SMGS Hospital, GMC Jammu from August 2017 to June 2019.A total of 20 patients of chronic otitis media with mastoid abscess were included in the study and were planned for mastoidectomy. In all patients, abscess drainage followed by modified radical mastoidectomy via post-aural approach was done in the same sitting. In all patients, the contents of abscess were sent for histo-pathological, microscopic examination and culture study. Results: Histopathological and microscopic examination of contents of abscess revealed bacterial aetiology (Staphylococcal aureus, Klebseilla pneumoniae) in 11 patients, cholesteatoma in 7 patients and tuberculosis in 2 patients. Conclusion: Mastoid abscess is an important complication of otitis media, requiring prompt diagnosis and intervention.